3D printing and sustainable product development - Ul Haq, Mir Irfan (CRC Press, Taylor & Francis Group, 2024)
The text focuses on the role and the importance of 3D printing in new product development processes. It covers various aspects such as the 3D printing revolution and Industry 4.0, sustainability and 3D printing, and economics of 3D printing. It discusses important concepts, including 3D printing, rapid prototyping, mechanical and physical properties of 3D printed parts, nanomaterials, and material aspects of 3D printing.Features1. Presents recent advances such as Industry 4.0, 4D printing, 3D material mechanical characterization, and printing of advanced materials.2. Highlights the interdisciplinary aspects of 3D printing, particularly in biomedical, and aerospace engineering.3. Discusses mechanical and physical properties of 3D printed parts, material aspects, and process parameters.4. Showcases topics such as rapid prototyping, medical equipment design, and biomimetics related to the role of 3D printing in new product development.5.Covers applications of 3D printing in diverse areas, including automotive, aerospace engineering, medical, and marine industry.It will serve as an ideal reference text for senior undergraduate, graduate students, and researchers in diverse engineering domains, including manufacturing, mechanical, aerospace, automotive, and industrial